Optymalna niejednorodność plastyczna skręcanego wycinka torusa - MIODUCHOWSKI, Andrzej (Engineering Transactions, 1971)
An optimal plastical inhomogeneity of a twisted scrap of torus In this paper an optimal dissolution of plastic inhomogeneity of a twisted scrap of torus is considered. Results were obtained by numerical means can be considered as practical suggestions for an engineer dealing with optimal problems in designing elements of constructions.